Use of dehydrated carrot (Daucus carota) pomace and almond (Prunus dulcis) powder for partial replacement of wheat flour in cake: effect on product quality and acceptability - Kausar, Tusneem; Laaraj, Salah; Hussain, Ashiq; Noutfia, Younes; Bouhrim, Mohamed; Mothana, Ramzi A.; Noman, Omar M.; Mubashar, Aymen; Firdous, Nida; Ali, Shafiqa; Yaqub, Shazia; Elfazazi, Kaoutar (Frontiers in Sustainable Food Systems, 2024)
Carrot (Daucus carota) is a nutrient-dense root vegetable, and carrot pomace is a by-product of the juice extraction procedure, which is recognized a source of phytochemicals and functional components. Almonds (Prunus dulcis) are packed with a decent amount of nutrients and bioactives. This study investigates the utilization of carrot pomace powder (CPP) and almond powder (AP) as partial substitutes for straight grade white flour (SGWF) in cakes to enhance their nutritional value and sensory appeal, while reducing waste from carrot processing. The aim is to assess the effects of incorporating CPP (at 5%, 10%, and 15%) and AP (at 5%) on the chemical composition and properties of cakes. Comparative analysis reveals that AP is rich in fat (13.8±0.6%) and protein (31±0.6%), while CPP excels in ash (5.0±0.5%) and fiber (43.3±3.3%) content. Furthermore, SGWF exhibits the highest moisture content. Water holding capacities for CPP and AP are 5.2±0.2% and 5.0±0.1%, respectively, and oil holding capacities are 1.3±0.1% and 1.8±0.2%, respectively. Additionally, CPP contains higher levels of sodium, potassium, and calcium, while AP contains higher levels of magnesium, iron, and zinc compared to SGWF. The addition of CPP and AP increases the ash, fat, fiber, and protein contents of the cakes. Notably, cakes containing 80% SGWF, 15% CPP, and 5% AP show significantly higher total phenolic content (TPC) (125.5±3.8 mg GAE/100 g), total flavonoid content (TFC) (58.4±1.4 mg QE/100 g), and DPPH activity (17.6±2.7%) compared to control cakes. Furthermore, a significant increment in mineral content is observed in cakes with high levels of CPP and AP. Sensory evaluations reveal high acceptance of cakes containing 15% CPP and 5% AP. In conclusion, this study suggests that the incorporation of CPP and AP into cakes can improve their nutritional profile, antioxidant activity, and sensory characteristics, offering a sustainable approach to bakery product development.